Self-Medication of Antibiotics Among Medical College Students of Chattogram (Journal of Chittagong Medical College Teachers' Association, 2019)
Background: The study was conducted to observe the prevalence of practice regarding self medication of antibiotics among medical students. Materials and methods: This was a cross-sectional, questionnaire-based study which was conducted among the preclinical phase, paraclinical phase and and clinical phase of medical students of four Medical College and Hospital in Chattogram. Total 120 students of four medical colleges participated in the study. Results: Total 120 undergraduates participated in the study. Among them 48(40%) were male and 72 (60%) were female. The prevalence of selfmedication among the medical students was 90(75%) whereas 30(25%) mentioned that they didn’t follow or encouraged selfmedication. The most important indication for antibiotic self-medication was cough and cold (60%) diarrhea (40%) then sore throat and dental infection (10%). The most common class of antibiotic self-medicated was Metronidazole (60%) followed by Azithromycin (53.33%) Amoxycillin 24(16%) and Erythromycin 20 (16.66%). Conclusions: This questionnaire based study revealed the higher prevalence of self-medication of antibiotics among the undergraduate especially in preclinical phase. The major and important reason for misuse of antibiotics is lack of proper knowledge on antibiotic resistance. It is important to spread the information and knowledge about antibiotic misuse by selfmedication and its consequent effects. Hence, incorporation of chapter in rational use of antibiotics becomes necessary and restrict the curriculum not only in Pharmacology undergraduate medical study but also should be included in the school books that can emphasizes more on the disadvantages of self medication of antibiotic.JCMCTA 2018 ; 29 (2) : 22-27